Social inequality : - Marger, Martin N. (McGraw-Hill, 2008)
This text provides an introduction to key concepts, current research findings, and theories in social inequality. While focusing primarily on social class, it also deals broadly with other forms of social inequality, including racial/ethnic, gender, and political. In dealing with the various dimensions of inequality, the book explains how they overlap and interrelate.